A method for manufacturing a pure adhesive film with low dielectric loss
By synthesizing polyimide resin and preparing specific glue, a pure adhesive film with low dielectric loss is made, which solves the problems of high dielectric loss value, low peel strength and poor heat resistance in the prior art, and realizes the dielectric loss value The reduction of solder heat resistance and peel strength are improved, and the chemical resistance is excellent.
Patent Information
- Application Number
- CN202211742381.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-29
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2042-12-29
AI Technical Summary
The existing low-dielectric loss cover films have problems such as large dielectric loss value, low peel strength, poor solder heat resistance and poor chemical resistance.
By synthesizing a prepolymer-polyamic acid solution of a thermoplastic polyimide resin with low dielectric loss, and preparing a glue containing an epoxy resin, a curing agent, a latent curing agent and a flame retardant, applied to PET On the film, a pure film with low dielectric loss is made by baking and pressing.
The dielectric loss value was reduced. The test value at 10GHz was about 0.003, the solder heat resistance was improved to 300℃/30s, the peel strength was ≥1.0kgf/cm, and the chemical resistance was excellent, and the peel strength decline rate was ≤10%.
Smart Images

Figure CN116285718B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of microelectronic materials, and in particular to a method for manufacturing a pure adhesive film with low dielectric loss. Background Art
[0002] As one of the materials of flexible copper clad laminate (FCCL), pure adhesive film is used in making multi-layer FPC boards and soft-hard combined FPC boards in flexible circuit boards (FPC), which plays the role of bonding two FPCs and prepares for subsequent circuit conduction. With the development of high-frequency FPC, such as high-speed FPC antennas and high-frequency data transmission lines, the demand for pure adhesive film with low dielectric loss is increasing.
[0003] like Figure 1 As shown in the figure, the structure of ordinary pure adhesive film is mainly composed of PET release film / adhesive / release paper, with a three-layer structure. The adhesive is mainly epoxy resin and acrylic acid. Ordinary pure adhesive film has the following defects:
[0004] 1. The dielectric loss value is relatively large, and the test value at 10GHz is about 0.01;
[0005] 2. Poor heat resistance of solder: it can only reach 260℃ / 10 seconds. Generally, when doing SMT soldering on soft boards, the temperature mostly exceeds 300℃. In addition, the pressing process temperature of multi-layer FPC boards and soft-hard combined FPC boards in production is also as high as 200℃. For ordinary pure adhesive films, these applications are not suitable and the use field is limited;
[0006] In recent years, in order to reduce dielectric loss, the following methods have been adopted:
[0007] Changing the composition of epoxy resin, such as replacing rubber and resin.
[0008] At present, the more serious problems of low dielectric loss cover films are:
[0009] 1. The dielectric loss value is relatively large, and the test value at 10GHz is about 0.007~0.01;
[0010] 2. Low peel strength: 0.3-0.5kgf / cm;
[0011] 3. Solder heat resistance is poor: can only reach 260℃ / 10 seconds;
[0012] 4. Poor chemical resistance: After the chemical resistance test, the peel strength decrease rate is greater than 20%. Summary of the invention
[0013] The object of the present invention is to provide a method for manufacturing a pure adhesive film with low dielectric loss to solve the problems raised in the above background technology.
[0014] To achieve the above object, the present invention provides the following technical solutions:
[0015] A method for manufacturing a pure adhesive film with low dielectric loss comprises the following steps:
[0016] Step 1, synthesizing a prepolymer of a thermoplastic polyimide resin with low dielectric loss - a polyamic acid solution;
[0017] Step 2, preparing glue: add the polyamic acid solution synthesized in step 1, epoxy resin YX8100BH30, epoxy resin NC-3000-H, curing agent CUA-4, latent curing agent boron trifluoride-2-methylimidazole, flame retardant SPB-100, solvent cyclohexanone, solvent butanone into the container of the PE bottle in sequence, then stir and stand for defoaming;
[0018] Step 3, take the glue prepared in step 2 and apply it on the PET release film;
[0019] Step 4: After coating, the coated PET release film is baked, and then the release surface of the release paper is pressed with a laminating machine, that is, the production of the pure adhesive film with low dielectric loss is completed and immediately stored in a cold storage.
[0020] Preferably, in the step 2, the PE bottle container has a capacity of 2000 ml, and the weight ratio of the polyamic acid solution, epoxy resin YX8100BH30, epoxy resin NC-3000-H, curing agent CUA-4, latent curing agent boron trifluoride-2-methylimidazole, flame retardant SPB-100, solvent cyclohexanone, and solvent butanone is 226:117:205:48:3:20:34:706, and stirring is carried out at a speed of 1000RPM for 2 hours in the step 2.
[0021] Preferably, in the step three, the model of the PET release film is 38E-NSD (H), the thickness of the PET release film is 38 um, and the thickness of the coated dry glue is one of 15-17 um or 25-27 um.
[0022] Preferably, the baking temperature in step 4 is 145-155°C, the baking time is 2-5 minutes, the laminating temperature of the laminating machine is 98-100°C, the model of the release paper is Taibo 130WE2D-TB, and the temperature of the cold storage is ≤5°C.
[0023] Preferably, the method for synthesizing the polyamic acid solution comprises the following steps:
[0024] ①In a three-necked container filled with nitrogen, add cyclohexanone solution and then add Priamine™ 1074, and stir mechanically at room temperature until completely dissolved;
[0025] ②Put the product of ① in an oil bath, add BTDA, and mechanically stir to dissolve to obtain polyamic acid resin;
[0026] ③ Take out the mechanical stirring in ②, put in the magnetic stirring, heat up to reflux, then stop stirring, cool to room temperature, and let stand to defoam.
[0027] Preferably, the oil bath temperature in ② is 67-73°C, and the room temperature in ① and ③ is 23-27°C.
[0028] Preferably, in step ③, the temperature is raised to 155-165° C. with magnetic stirring, and the reflux time is 3.5-4.5 hours.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] 1. The dielectric loss value is low, and the test value at 10GHz is about 0.003;
[0031] 2. Good heat resistance: solder heat resistance is 300℃ / 30s;
[0032] 3. Peel strength ≥1.0kgf / cm;
[0033] 4. Excellent chemical resistance: After the chemical resistance test, the peel strength decrease rate is ≤10%: The chemical resistance is quite excellent, and the peel strength does not decrease significantly after long-term immersion in chemical reagents (isopropyl alcohol, 2mol / L hydrochloric acid, 2mol / L sodium hydroxide solution). BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Further details, features and advantages of the invention are disclosed in the following description of exemplary embodiments in conjunction with the accompanying drawings, in which:
[0035] Figure 1 A schematic diagram of the prior art according to the present invention is shown; DETAILED DESCRIPTION
[0036] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] A method for manufacturing a pure adhesive film with low dielectric loss in this embodiment includes the following steps:
[0038] Step 1, synthesizing a prepolymer of a thermoplastic polyimide resin with low dielectric loss - a polyamic acid solution;
[0039] Step 2, preparing glue: add the polyamic acid solution synthesized in step 1, epoxy resin YX8100BH30, epoxy resin NC-3000-H, curing agent CUA-4, latent curing agent boron trifluoride-2-methylimidazole, flame retardant SPB-100, solvent cyclohexanone, solvent butanone into the container of the PE bottle in sequence, then stir and stand for defoaming;
[0040] Step 3, take the glue prepared in step 2 and apply it on the PET release film;
[0041] Step 4: After coating, the coated PET release film is baked, and then the release surface of the release paper is pressed with a laminating machine, that is, the production of the pure adhesive film with low dielectric loss is completed and immediately stored in a cold storage.
[0042] In step 2 of this embodiment, the PE bottle container has a capacity of 2000 ml, and the weight ratio of polyamic acid solution, epoxy resin YX8100BH30, epoxy resin NC-3000-H, curing agent CUA-4, latent curing agent boron trifluoride-2-methylimidazole, flame retardant SPB-100, solvent cyclohexanone, and solvent butanone is 226:117:205:48:3:20:34:706. In step 2, stirring is carried out at a speed of 1000RPM for 2 hours.
[0043] In step 3 of this embodiment, the model of the PET release film is 38E-NSD (H), the thickness of the PET release film is 38um, and the thickness of the applied dry glue is one of 15-17um or 25-27um.
[0044] In step 4 of this embodiment, the baking temperature is 145-155°C, the baking time is 2-5 minutes, the laminating temperature of the laminating machine is 98-100°C, the model of the release paper is Taibo 130WE2D-TB, and the temperature of the cold storage is ≤5°C.
[0045] The synthesis method of the polyamic acid solution of the present embodiment comprises the following steps:
[0046] ①In a three-necked container filled with nitrogen, add cyclohexanone solution and then add Priamine™ 1074, and stir mechanically at room temperature until completely dissolved;
[0047] ②Put the product of ① in an oil bath, add BTDA, and mechanically stir to dissolve to obtain polyamic acid resin;
[0048] ③ Take out the mechanical stirring in ②, put in the magnetic stirring, heat up to reflux, then stop stirring, cool to room temperature, and let stand to defoam.
[0049] The oil bath temperature in ② of this embodiment is 67-73°C, and the room temperature in ① and ③ is 23-27°C.
[0050] In ③ of this embodiment, the temperature is raised to 155-165° C. with magnetic stirring, and the reflux time is 3.5-4.5 hours. Example 1
[0051] A method for manufacturing a pure adhesive film with low dielectric loss comprises the following steps:
[0052] Step 1, synthesizing a prepolymer of a thermoplastic polyimide resin with low dielectric loss - a polyamic acid solution;
[0053] Step 2, preparing glue: add the polyamic acid solution synthesized in step 1, epoxy resin YX8100BH30, epoxy resin NC-3000-H, curing agent CUA-4, latent curing agent boron trifluoride-2-methylimidazole, flame retardant SPB-100, solvent cyclohexanone, solvent butanone into the container of the PE bottle in sequence, then stir and stand for defoaming;
[0054] Step 3, take the glue prepared in step 2 and apply it on the PET release film;
[0055] Step 4: After coating, the coated PET release film is baked, and then the release surface of the release paper is pressed with a laminating machine, that is, the production of the pure adhesive film with low dielectric loss is completed and immediately stored in a cold storage.
[0056] In step 2 of this embodiment, the PE bottle container has a capacity of 2000 ml, and the weight ratio of polyamic acid solution, epoxy resin YX8100BH30, epoxy resin NC-3000-H, curing agent CUA-4, latent curing agent boron trifluoride-2-methylimidazole, flame retardant SPB-100, solvent cyclohexanone, and solvent butanone is 226:117:205:48:3:20:34:706. In step 2, stirring is carried out at a speed of 1000RPM for 2 hours.
[0057] In step 3 of this embodiment, the model of the PET release film is 38E-NSD (H), the thickness of the PET release film is 38 um, and the thickness of the applied dry glue is 15 um.
[0058] In step 4 of this embodiment, the baking temperature is 145° C., the baking time is 2 minutes, the laminating temperature of the laminating machine is 98° C., the model of the release paper is Taibo 130WE2D-TB, and the temperature of the cold storage is ≤5° C.
[0059] The synthesis method of the polyamic acid solution of the present embodiment comprises the following steps:
[0060] ①In a three-necked container filled with nitrogen, add cyclohexanone solution and then add Priamine™ 1074, and stir mechanically at room temperature until completely dissolved;
[0061] ②Put the product of ① in an oil bath, add BTDA, and mechanically stir to dissolve to obtain polyamic acid resin;
[0062] ③ Take out the mechanical stirring in ②, put in the magnetic stirring, heat up to reflux, then stop stirring, cool to room temperature, and let stand to defoam.
[0063] The oil bath temperature in ② of this embodiment is 67°C, and the room temperature in ① and ③ is 23°C.
[0064] In ③ of this embodiment, the temperature was raised to 155° C. with magnetic stirring, and the reflux time was 3.5 hours. Example 2
[0065] A method for manufacturing a pure adhesive film with low dielectric loss comprises the following steps:
[0066] Step 1, synthesizing a prepolymer of a thermoplastic polyimide resin with low dielectric loss - a polyamic acid solution;
[0067] Step 2, preparing glue: add the polyamic acid solution synthesized in step 1, epoxy resin YX8100BH30, epoxy resin NC-3000-H, curing agent CUA-4, latent curing agent boron trifluoride-2-methylimidazole, flame retardant SPB-100, solvent cyclohexanone, solvent butanone into the container of the PE bottle in sequence, then stir and stand for defoaming;
[0068] Step 3, take the glue prepared in step 2 and apply it on the PET release film;
[0069] Step 4: After coating, the coated PET release film is baked, and then the release surface of the release paper is pressed with a laminating machine, that is, the production of the pure adhesive film with low dielectric loss is completed and immediately stored in a cold storage.
[0070] In step 2 of this embodiment, the PE bottle container has a capacity of 2000 ml, and the weight ratio of polyamic acid solution, epoxy resin YX8100BH30, epoxy resin NC-3000-H, curing agent CUA-4, latent curing agent boron trifluoride-2-methylimidazole, flame retardant SPB-100, solvent cyclohexanone, and solvent butanone is 226:117:205:48:3:20:34:706. In step 2, stirring is carried out at a speed of 1000RPM for 2 hours.
[0071] In step 3 of this embodiment, the model of the PET release film is 38E-NSD (H), the thickness of the PET release film is 38 um, and the thickness of the applied dry glue is 17 um.
[0072] In step 4 of this embodiment, the baking temperature is 155° C., the baking time is 5 minutes, the laminating temperature of the laminating machine is 100° C., the model of the release paper is Taibo 130WE2D-TB, and the temperature of the cold storage is ≤5° C.
[0073] The synthesis method of the polyamic acid solution of the present embodiment comprises the following steps:
[0074] ①In a three-necked container filled with nitrogen, add cyclohexanone solution and then add Priamine™ 1074, and stir mechanically at room temperature until completely dissolved;
[0075] ②Put the product of ① in an oil bath, add BTDA, and mechanically stir to dissolve to obtain polyamic acid resin;
[0076] ③ Take out the mechanical stirring in ②, put in the magnetic stirring, heat up to reflux, then stop stirring, cool to room temperature, and let stand to defoam.
[0077] The oil bath temperature in ② of this embodiment is 73°C, and the room temperature in ① and ③ is 27°C.
[0078] In ③ of this embodiment, the temperature was raised to 165° C. with magnetic stirring, and the reflux time was 4.5 hours. Example 3
[0079] A method for manufacturing a pure adhesive film with low dielectric loss comprises the following steps:
[0080] Step 1, synthesizing a prepolymer of a thermoplastic polyimide resin with low dielectric loss - a polyamic acid solution;
[0081] Step 2, preparing glue: add the polyamic acid solution synthesized in step 1, epoxy resin YX8100BH30, epoxy resin NC-3000-H, curing agent CUA-4, latent curing agent boron trifluoride-2-methylimidazole, flame retardant SPB-100, solvent cyclohexanone, solvent butanone into the container of the PE bottle in sequence, then stir and stand for defoaming;
[0082] Step 3, take the glue prepared in step 2 and apply it on the PET release film;
[0083] Step 4: After coating, the coated PET release film is baked, and then the release surface of the release paper is pressed with a laminating machine, that is, the production of the pure adhesive film with low dielectric loss is completed and immediately stored in a cold storage.
[0084] In step 2 of this embodiment, the PE bottle container has a capacity of 2000 ml, and the weight ratio of polyamic acid solution, epoxy resin YX8100BH30, epoxy resin NC-3000-H, curing agent CUA-4, latent curing agent boron trifluoride-2-methylimidazole, flame retardant SPB-100, solvent cyclohexanone, and solvent butanone is 226:117:205:48:3:20:34:706. In step 2, stirring is carried out at a speed of 1000RPM for 2 hours.
[0085] In step 3 of this embodiment, the model of the PET release film is 38E-NSD (H), the thickness of the PET release film is 38 um, and the thickness of the applied dry glue is 16 um.
[0086] In step 4 of this embodiment, the baking temperature is 150° C., the baking time is 3 minutes, the laminating temperature of the laminating machine is 99° C., the model of the release paper is Taibo 130WE2D-TB, and the temperature of the cold storage is ≤5° C.
[0087] The synthesis method of the polyamic acid solution of the present embodiment comprises the following steps:
[0088] ①In a three-necked container filled with nitrogen, add cyclohexanone solution and then add Priamine™ 1074, and stir mechanically at room temperature until completely dissolved;
[0089] ②Put the product of ① in an oil bath, add BTDA, and mechanically stir to dissolve to obtain polyamic acid resin;
[0090] ③ Take out the mechanical stirring in ②, put in the magnetic stirring, heat up to reflux, then stop stirring, cool to room temperature, and let stand to defoam.
[0091] The oil bath temperature in ② of this embodiment is 70°C, and the room temperature in ① and ③ is 25°C.
[0092] In ③ of this embodiment, the temperature was raised to 160° C. with magnetic stirring, and the reflux time was 4 hours.
[0093] The chemical materials used to prepare the intermediate pre-solution in the invention are as follows:
[0094] 1. Priamine™ 1074 diamine: purchased from Croda, UK;
[0095] 2. BTDA (3,3',4,4'-benzophenone tetracarboxylic dianhydride): purchased from Shanghai Li Luo Industrial Co., Ltd.;
[0096] 3. Cyclohexanone: solvent, electronic grade, purity ≥ 99.8%, water content ≤ 0.08%. Purchased from Liaocheng Meisi New Material Technology Co., Ltd.
[0097] The chemical materials used to prepare glue are as follows:
[0098] 1.YX8100BH30: epoxy resin, purchased from Mitsubishi Chemical, Japan;
[0099] 2. NC-3000-H: epoxy resin, purchased from Nippon Kayaku;
[0100] 3. CUA-4: curing agent, purchased from IHARA Chemical industry co., ltd., Japan;
[0101] 4. Boron trifluoride-2-methylimidazole: latent curing agent, purchased from Dongying Heyi Chemical Co., Ltd.;
[0102] 5.SPB-100: flame retardant, purchased from Otsuka Chemical of Japan.
[0103] 6. Butanone: solvent, electronic grade, purity ≥ 99.7%, water content ≤ 0.3%, purchased from Dongguan Baibaishun Petrochemical Co., Ltd.;
[0104] The coating materials are as follows:
[0105] 1. PET release film: Model 38E-NSD(H), manufacturer: Japan Fujimori Industries Co., Ltd. (ZACROS)
[0106] 2. Release paper: model 130WE2D-TB, manufacturer: Kunshan Taibo Adhesive Materials Co., Ltd.
[0107] Synthesis example
[0108] 1. Preparation of polyamide acid solution, the precursor of thermoplastic polyimide resin with low dielectric loss:
[0109] ① In a three-necked container filled with nitrogen, add 157.44 g of cyclohexanone solution, and then add 43.2 g (0.08 mol)
[0110] Priamine™ 1074, dissolved completely by mechanical stirring at room temperature (25°C);
[0111] ② Place the product of the first step in an oil bath at 70°C, add 25.78 g (0.08 mol) of BTDA, and stir mechanically to dissolve to obtain a polyamic acid resin.
[0112] ③Take out the mechanical stirring in ②, put in the magnetic stirring, heat to 160℃, reflux for 4 hours, then stop stirring.
[0113] After cooling to room temperature (25°C) and standing to defoam, the resin solid content was measured to be 30.5% and the viscosity was 552 CPS.
[0114] 2. Preparation of glue:
[0115] In a 2000 ml PE bottle, 226.42 g of the polyamic acid solution synthesized in step 1, 117.16 g of epoxy resin YX8100BH30, 205.12 g of epoxy resin NC-3000-H, 48.12 g of curing agent (CUA-4), 2.44 g of latent curing agent (boron trifluoride-2-methylimidazole), 20.26 g of flame retardant (SPB-100), 33.6 g of solvent (cyclohexanone), and 706 g of solvent (butanone) were added in sequence, and then stirred at a speed of 1000 RPM for 2 hours, and then allowed to stand for defoaming. The resin solid content was measured to be 35.2% and the viscosity was 310 CPS. Example 4
[0116] Preparation and performance testing of 15um thick low dielectric loss pure adhesive film
[0117] ⑴ Take the above glue and apply it on a 38um thick PET release film. The model of the PET release film is 38E-NSD (H). The thickness of the applied dry glue is 15-17um. The coating process: the width of the cut PET release film is 295mm, the laboratory automatic coating machine, the speed is set to 505RPM, and a 0.16mm scraper is used;
[0118] ⑵After coating, bake at 150℃ for 3 minutes, and then use a laminating machine at 100℃ to press the release surface of the release paper. The model of the release paper is Taibo 130WE2D-TB. After the pure adhesive film is made, it should be stored in a cold storage (≤5℃) immediately;
[0119] ⑶ Preparation of test samples:
[0120] Test: The laminated substrate is the PI surface of Doosan's glue-free single-sided board. The model of Doosan's glue-free single-sided board is Dsflex-600 122500EP(C)250(L), which is a glue-free electrolytic copper single-sided board by coating method. The structure is (12um electrolytic copper foil + 25um thick PI film). The glue-free single-sided board should be baked at 80℃ for 30 minutes for dehumidification before use.
[0121] During the test, first tear off the pure adhesive release paper, and use a laminating machine to press the remaining adhesive surface with the PI surface of the above Doosan non-adhesive single-sided board at 100°C, then tear off the pure adhesive PET release film surface, and use a laminating machine to press the adhesive surface with the PI surface of the above Doosan non-adhesive single-sided board at 100°C, and then use a fast press to press. Laminating conditions: temperature: 180°C, molding pressure 100kgf / cm2, pre-pressing time: 10 seconds, molding pressing time: 60 seconds, pre-pressing pressure: 10kgf / cm2. After pressing, bake at 170°C for two hours;
[0122] ⑷Performance test:
[0123] ①Tin heat resistance (strictly tested according to IPC-TM-650 2.4.13 method) (300℃ / 30s), four pieces were tested and all passed;
[0124] ② Peel strength (3.175mm line width): MD direction: 1.37kgf / cm, TD direction: 1.23kgf / cm, both performances are qualified;
[0125] ③ Chemical resistance: Take the peel strength test piece and soak it in the following chemicals: isopropyl alcohol, 2mol / L hydrochloric acid, 2mol / L sodium hydroxide solution, in that order for 210 seconds each. Take it out and dry it. Test the peel strength. The results show that the MD direction is 1.31kgf / cm, the TD direction is 1.21kgf / cm, and the peel strength decrease rate is ≤10%. The performance is qualified.
[0126] ④Dielectric constant and dielectric loss:
[0127] Three groups of test pieces were tested, and three groups of test values were obtained:
[0128] a. Dielectric constant: 2.90, dielectric loss: 0.0030;
[0129] b. Dielectric constant: 2.89, dielectric loss: 0.0032;
[0130] c. Dielectric constant: 2.90, dielectric loss: 0.0031; Example 5
[0131] Preparation and performance testing of 25um thick low dielectric loss pure adhesive film
[0132] ⑴ Take the above glue and apply it on a 38um thick PET release film. The model of the PET release film is 38E-NSD (H). The thickness of the applied dry glue is 25-27um. The coating process: the width of the cut PET release film is 295mm, the laboratory automatic coating machine, the speed is set to 505RPM, and a 0.2mm scraper is used;
[0133] ⑵After coating, bake at 150℃ for 3 minutes, and then use a laminating machine at 100℃ to press the release surface of the release paper. The model of the release paper is Taibo 130WE2D-TB. After the pure adhesive film is made, it should be stored in a cold storage (≤5℃) immediately;
[0134] ⑶ Preparation of test samples:
[0135] Test: The laminated substrate is the PI surface of Doosan's glue-free single-sided board. The model of Doosan's glue-free single-sided board is Dsflex-600 122500EP(C)250(L), which is a glue-free electrolytic copper single-sided board by coating method. The structure is (12um electrolytic copper foil + 25um thick PI film). The glue-free single-sided board should be baked at 80℃ for 30 minutes for dehumidification before use.
[0136] During the test, first tear off the release paper of the pure adhesive film, and use a laminating machine to press the remaining adhesive surface to the PI surface of the above Doosan adhesive-free single-sided board at 100°C, then tear off the pure adhesive PET release film, and use a laminating machine to press the adhesive surface to the PI surface of the above Doosan adhesive-free single-sided board at 100°C. Finally, use a fast press to press. Laminating conditions: temperature: 180°C, molding pressure 100kgf / cm2, pre-pressing time: 10 seconds, molding pressing time: 60 seconds, pre-pressing pressure: 10kgf / cm2. After laminating, bake at 170°C for two hours;
[0137] ⑷Performance test:
[0138] ①Solder heat resistance (strictly tested according to IPC-TM-650 2.4.13 method) (300℃ / 30s), four pieces were tested and all passed;
[0139] ② Peel strength (3.175mm line width): MD direction: 1.99kgf / cm, TD direction: 1.89kgf / cm, both performances are qualified;
[0140] ③ Chemical resistance: Take the peel strength test piece and soak it in the following chemicals: isopropyl alcohol, 2mol / L hydrochloric acid, 2mol / L sodium hydroxide solution, in order, soak it in the reagents for 210 seconds each, take it out and dry it, test the peel strength, and the measured results are MD direction: 1.93kgf / cm, TD direction: 1.83kgf / cm, the peel strength decrease rate is ≤10%, and the performance is qualified;
[0141] ④Dielectric constant and dielectric loss:
[0142] Three groups of test pieces were tested, and three groups of test values were obtained:
[0143] a. Dielectric constant: 2.88, dielectric loss: 0.0031;
[0144] b. Dielectric constant: 2.90, dielectric loss: 0.0030;
[0145] c. Dielectric constant: 2.89, dielectric loss: 0.0032;
[0146] The test instruments, test standards and methods in this invention are as follows:
[0147] 1. Thickness: tested by Japanese NIKON MS-4G altimeter, accurate to 0.1um:
[0148] 2. Peel strength: tested using Japan Shimadzu AG-1 universal tensile machine
[0149] Based on standard: IPC-TM-650, Method 2.4.9
[0150] Stretching speed: 50mm / min
[0151] Test piece width: 3.175mm
[0152] Test piece test distance: 70mm
[0153] 90 degree roller test
[0154] 3. Dielectric constant and dielectric loss
[0155] The test was conducted using the E5071C ENA network analyzer and N9030A separated dielectric resonator (SPDR) from Keysight Technologies (China).
[0156] Constant temperature and humidity machine: KTHA-415TBS model from Qingsheng, Taiwan, China;
[0157] Based on standard: IPC-TM-650 2.5.5.3
[0158] Test method: Place the etched PI film specimen of 81.3mm×81.3mm in a constant temperature and humidity chamber at 23℃ and 50% RH for 24h, laminate it to a thickness of 0.4mm, adjust the frequency of the high resistance meter to 10GHz and then measure it.
[0159] 4. Electronic balance
[0160] Model: LT1002, Manufacturer: Changshu Tianliang Instrument Co., Ltd. Maximum weighing: 1000g, Accuracy: 0.01g
[0161] 5. Soldering heat resistance
[0162] Tested using the YSC solder furnace from Taiwan's Yongli Technology Co., Ltd.
[0163] Based on standard: IPC-TM-650 2.4.13
[0164] Test conditions: The test piece is baked at 135℃ for 1h and then immersed in a tin furnace to observe its changes.
[0165] 6. Solid content of glue:
[0166] Instrument used: Mettler-Toledo HG53 moisture analyzer
[0167] Test conditions: Weigh 2±0.1g of resin, incubate at 160℃, 180℃ or 190℃, wait until the mass becomes constant for 1 minute, and then read the value.
[0168] 7. Viscosity of glue:
[0169] Instrument used: BROOKFIELD LVDV-I+ Rotational Viscometer
[0170] Test conditions: Keep in a water bath at 25°C for more than 30 minutes before testing.
[0171] 8. Chemical resistance:
[0172] Based on standard: IPC-TM-650 2.3.2 Method A.
[0173] 9. Automatic coating machine:
[0174] Adopt Taiwan Huanyang Precision Machinery automatic translation coating machine.
[0175] 10. Laboratory magnetic stirrer:
[0176] Manufacturer: Gongyi Yuhua Instrument Co., Ltd., Model: DF-101T collector constant temperature heating magnetic stirrer.
[0177] 11. Laboratory high-speed mixer
[0178] Equipment name: Digital display constant speed powerful electric mixer
[0179] Manufacturer: Shanghai Specimen Model Factory, Model: JB300-SH disperser.
[0180] 12. The test samples were made using the FPC fast pressing machine of Zhuhai Bion Electronic Equipment Co., Ltd., model: BAT-80T-01A, and the parameter settings are as follows: pressing conditions: temperature: 180°C, molding pressure 100kgf / cm2, pre-pressing time: 10 seconds, pressing time: 60 seconds, pre-pressing pressure: 10kgf / cm2.
[0181] 13. Oven: Manufacturer: Zhisheng, Taiwan, China, Model: SMO-1B, maximum temperature can reach 200℃.
[0182] 14. Laminating machine: Manufacturer: Xiangmeng, Model: HK 330S, the highest temperature can reach 200℃.
[0183] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0184] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for manufacturing a pure adhesive film with low dielectric loss, characterized in that: The following steps are involved: Step 1, synthesizing a prepolymer of a thermoplastic polyimide resin with low dielectric loss - a polyamic acid solution; Step 2, preparing glue: add the polyamic acid solution synthesized in step 1, epoxy resin YX8100BH30, epoxy resin NC-3000-H, curing agent CUA-4, latent curing agent boron trifluoride-2-methylimidazole, flame retardant SPB-100, solvent cyclohexanone, solvent butanone into the container of the PE bottle in sequence, then stir and stand for defoaming; Step 3, take the glue prepared in step 2 and apply it on the PET release film; Step 4: After coating, the coated PET release film is baked, and then the release surface of the release paper is pressed with a laminating machine, that is, the pure adhesive film with low dielectric loss is completed and immediately stored in a cold storage; In the step 2, the PE bottle container has a capacity of 2000 ml, and the weight ratio of the polyamic acid solution, epoxy resin YX8100BH30, epoxy resin NC-3000-H, curing agent CUA-4, latent curing agent boron trifluoride-2-methylimidazole, flame retardant SPB-100, solvent cyclohexanone, and solvent butanone is 226:117:205:48:3:20:34:
706. In the step 2, the mixture is stirred at a speed of 1000 RPM for 2 hours. The synthesis method of the polyamic acid solution comprises the following steps: ①In a three-necked container filled with nitrogen, add cyclohexanone solution and then add Priamine™ 1074, and stir mechanically at room temperature until completely dissolved; ②Put the product of ① in an oil bath, add BTDA, and mechanically stir to dissolve to obtain polyamic acid resin; ③ Take out the mechanical stirring in ②, put in the magnetic stirring, heat up to reflux, then stop stirring, cool to room temperature, and let stand to defoam.
2. The method for manufacturing a pure adhesive film with low dielectric loss according to claim 1, characterized in that: In the step 3, the model of the PET release film is 38E-NSD (H), the thickness of the PET release film is 38um, and the thickness of the applied dry glue is one of 15-17um or 25-27um.
3. The method for manufacturing a pure adhesive film with low dielectric loss according to claim 1, characterized in that: The baking temperature in step 4 is 145-155° C., the baking time is 2-5 minutes, the laminating temperature of the laminating machine is 98-100° C., the model of the release paper is Taibo 130WE2D-TB, and the temperature of the cold storage is ≤5° C.
4. The method for manufacturing a pure adhesive film with low dielectric loss according to claim 1, characterized in that: The oil bath temperature in ② is 67-73°C, and the room temperature in ① and ③ is 23-27°C.
5. The method for manufacturing a pure adhesive film with low dielectric loss according to claim 1, characterized in that: In the step ③, the temperature is raised to 155-165° C. with magnetic stirring, and the reflux time is 3.5-4.5 hours.
Citation Information
Patent Citations
Low-dielectric-constant adhesive for flexible printed circuit boards and application method thereof
CN105778848A
Composite adhesive, flexible copper-clad plate and preparation method thereof
CN114015409A
Cited By
Pure adhesive film and preparation method thereof
CN121471834A